The effects of acute whole body vibration as a recovery modality following high-intensity interval training in well-trained, middle-aged runners - Edge, J.; Mündel, T.; Weir, K.; Cochrane, D. J. (European Journal of Applied Physiology, 2009)
The main purpose of the present study was to examine the effects of acute whole body vibration (WBV) on recovery following a 3 km time trial (3 km TT) and high-intensity interval training (HIIT) (8 × 400 m). Post-HIIT measures included 3 km time-trial performance, exercise metabolism and markers of muscle damage (creatine kinase, CK) and inflammation (c-reactive protein, CRP). A second purpose was to determine the effects of a 3 km TT and HIIT on performance and metabolism the following day. Nine well-trained, middle-aged, male runners [(mean ± SD) age 45 ± 6 years, body mass 75 ± 7 kg, [VO2peak 58 ± 5 ml/kgmin] performed a constant pace run at 60 and 80% velocity at VO2peak (v VO2peak) followed by a 3-km TT and a 8 × 400-m HIIT session on two occasions. Following one occasion, the athletes performed 2 × 15 min of low frequency (12 Hz) WBV, whilst the other occasion was a non-WBV control. Twenty-four hours after each HIIT session (day 2) participants performed the constant pace run (60 and 80% v [(V)\dot]VO2peak) and 3 km TT again. There was a significant decrease in 3 km TT performance (~10 s) 24 h after the HIIT session (P < 0.05); however, there were no differences between conditions (control vs. vibration, P > 0.05). Creatine kinase was significantly elevated on day 2, though there were no differences between conditions (P > 0.05). VO2 and blood lactate were lower on day 2 (P < 0.05), again with no differences between conditions (P > 0.05). These results show no benefit of WBV on running performance recovery following a HIIT session. However, we have shown that there may be acute alterations in metabolism 24 h following such a running session in well-trained, middle-aged runners.